Overview of approaches and methods - Kartawinata, K.; Sheil, Douglas; Wollenberg, Eva Karoline; Levang, P.; Sist, P. (CIFOR and ITTO, 2002)
The CIFOR-ITTO project's general objective is to achieve long-term forest management for multiple uses, integrating social and silvicultural objectives in Malinau, Kalimantan, Indonesia. To achieve this objective there are complicated issues to be dealt with and requires integrated research that combined biological and socioeconomics aspects. The underlying issue is: what are the appropriate research methods and conceptual approaches to guide sustainability for a large forest landscape, where diverse, rapidly changing and often conflicting land use demand exist? This chapter provides a comprehensive coverage of the main issues and perspective of the basic assessment of existing conditions and trends. The approaches adobted in the implementation of the project on reduced impact logging (RIL) technique, biodiversity multidisciplinary landscape assessment (MLA), forest product dependency and adaptive co-management of forests are described.